Where were you while we were getting high policing? The consequences of co-location for broader partnership working in tackling organised crime and terrorism - Atkinson, Colin (Policing and society, 2019)
The Scottish Crime Campus (SCC) represents a significant financial and political investment in policing organised crime and terrorism in Scotland. The ethos of physically co-locating high-policing agencies and promoting partnership working has been central to the SCC; however, the consequences for those agencies and actors not permanently based here have hitherto been overlooked. Based on mixed methods research this study considers the range of ‘outside’ partners who work with the core SCC-based agencies, and explores the consequences of these co-location arrangements for broader partnership working across this ‘new network’ of high policing. It finds that these 'outside' partners report a range of positive benefits from engaging with the SCC: from improvements in the quality and depth of partnership working to enhanced service delivery in their own work. The SCC has deepened collaboration between the crime campus-based agencies and those partners who directly participate, albeit in a more limited fashion, in these co-location arrangements. Partnership working with agencies fully ‘beyond’ the crime campus, however, is better characterised as co-operative, not collaborative. Extending collaboration further across this network would bring further benefits, but requires the addressing of boundary issues, including challenges of insularity and isolation, that can result from co-location.